ANALYSIS OF THE IMPACT OF DIGITAL MARKETING STRATEGIES IN INVESTIGATION ON ECONOMIC GROWTH - Fauzan Fadlullah; Sabo Hermawan; Shandy Aditya; Alifah Nur Rahmawati; Cornellius Seno Adriano (LPPM STIE Muhammadiah Bandung, 2025)
This study investigates the impact of digital marketing strategies within Indonesia’s burgeoning social commerce sector on national economic growth during 2020–2025. Indonesia, characterized by rapid digital transformation and a growing digital economy valued at USD 124 billion by 2025, faces challenges such as regional disparities and limited digital marketing adoption among MSMEs. To address the research gap on empirical analysis of digital marketing effectiveness in social commerce, this study employs a pragmatist mixed-methods approach. Quantitative data from large-scale surveys (1,750+ respondents) and secondary sources were analyzed using Structural Equation Modeling (SEM), complemented by qualitative interviews and focus group discussions for contextual insights. The SEM results demonstrate that six key digital marketing strategies—Customer Relationship Management (CRM), Brand Communication, Customer Engagement, Data-Driven Decision Making, Pricing Strategy, and Product Development—positively and significantly influence economic growth. CRM emerged as the strongest driver, highlighting the importance of customer retention and personalized engagement, followed by pricing strategy and product innovation. Correlation analysis revealed synergistic and occasionally conflicting relationships among these strategies, underscoring the complexity of digital marketing ecosystems. The findings affirm that a strategic blend of customer-focused, innovative, and data-informed practices fosters sustainable economic performance and supports MSME growth and job creation. This study contributes to academic literature by providing multi-dimensional evidence from an emerging digital economy and offers practical implications for policymakers, businesses, and platform operators aiming to optimize social commerce’s role in inclusive economic development in Indonesia.to maximize its positive impact on national economic growth in the digital era.